Emotional Expression and Health : Advances in Theory, Assessment and Clinical Applications. - Temoshok, Lydia; Vingerhoets, Ad (Taylor & Francis, 2004)
Emotional Expression and Health covers the major themes that are important for gaining insight into the role emotional expression and inhibition may play in staying healthy or falling ill.